Modeling Growth Kinetics of Methane Hydrate in Stirred Tank Batch Reactors - Gootam, Divya; Gaikwad, Namrata; Kumar, Rajnish; Kaisare, Niket (ACS Engineering Au, 2021)
Hydrate formation could be looked upon as multicomponent and multiphase reaction which is heavily dependent on mass transfer and heat transfer limitations even under favorable thermodynamic conditions. Gas uptake measurement is one of the easiest ways to understand the kinetics of hydrate growth. In a typical gas uptake measurement, one could easily observe three phases of hydrate formation: in phase-I, hydrate forming gas dissolves in the liquid phase which leads to hydrate nucleation; in phase-II, fast hydrate growth is observed; and in phase-III, hydrate grows slowly for relatively longer time periods. In a batch reactor, a slow down in hydrate growth rate as seen in phase-III is either due to a drop in the pressure of the reactor during hydrate growth and/or reduced mass transfer due to hydrate accumulation at the interface. In this work, a model is developed to predict phase-II events. The model proposed is based on an earlier model available in the literature which captured the intrinsic kinetics of gas hydrate growth for a semibatch reactor. Model discussed in the current study works for batch and semibatch reactor, it captures the kinetics for different stirrer speeds, water to gas ratios and different thermodynamic conditions. Experimental validation was done in a batch reactor at 274 K and 6 MPa with methane as the hydrate forming gas. A batch reactor with two different stirrer arrangements, different water-to-gas ratios, and different stirrer speeds were considered, and the mass transfer limitations for both the reactor configurations were studied. Further, a comparison study with the existing model and the modified model (current study) showed that the current model can be extended to other reactor types.